Pakistan in the Crosshairs and the Rising Stakes of Strategic Information Warfare - Dr. Sahibzada Muhammad Usman (National University of Modern Languages (NUML), Islamabad, 2024)
Over the past two decades, information and communication technologies (ICTs) have reaped significant attention from security experts, computer scientists, intelligence agencies, and governments for their potential applications in conflict scenarios. Using ICTs for offensive or defensive purposes to instantly invade, disrupt, or control the opponent's resources is known as strategic information warfare (SIW). Although SIW is as ancient as military history, the communication sciences revolution has altered its character. It has evolved into a double-edged weapon that is equally crucial for strong nations, technically underdeveloped states, non-state entities, and individual software experts. Some nations, most notably the US, Russia, and China, have taken the SIW technology seriously and compared it to the danger posed by WMDs. In the south Asian context, Pakistan faces a direct threat from India, which collaborates closely with Israel, by the use of SIW. Additionally, the Western media portrays a highly negative picture of Pakistan's administration, law and order, and economy. The national media, suitably supported by foreign players, has begun a propaganda warfare effort against Pakistan's military forces and intelligence institutions. However, SIW is now a global danger, necessitating a worldwide response. Pakistan must create a proactive national strategy to prepare for the problems erupted from SIW strike on the communication network, which is crucial for the operation of its nuclear facilities.